Application of quercetin flavonoid based hybrid nanocomposites: A review - Biswajit Parhi; Debasrita Bharatiya; Sarat K Swain (Elsevier, 2020)
Natural bioflavonoids are an essential component of dietary supplements possessing antimicrobial properties. Many of the bioflavonoids have resulted in positive antitumor, anticancer, antibacterial, antifungal, anti-inflammatory properties, but the efficacy remains low due to toxicity at the molecular level whereas antiviral property limits to negative. The synergistic link between nanoscience and flavonoid chemistry enhances the epidemiological properties of flavonoid and also diminish the antimicrobial resistivity (AMR) by forming their hybrid nanocomposites. Nanochemistry uses various nanocomposite and nanomaterials for biosensing the flavonoids and their delivery as a drug. The quercetin flavonoid and its derivatives such as rutin, and myricetin are used for sensing and drug delivery. Quercetin with 15Carbon-5Hydroxyl chemical scaffold has been explored for a few decades for the development of hybrid nanocomposite and nanomaterial with metallic as well as organic nano co-composites. This quercetin flavonoid based hybrid nanocomposites seemed to show a significant effect on In vitro and some animal model processes along with attenuating lipid peroxidation, platelet aggregation, and capillary permeability actions. This review mainly focused on the hybrid nanoscience of quercetin bioflavonoid and its application in numerous biological, material fields with a future perspective.